Lectura y análisis de textos informativos (noticias) para mejorar la competencia lectora en estudiantes de primaria - Mezarino Tarazona, Sendy Jessy (2021)
The aim of this paper is to support, theoretically and pedagogically, the reading and textual comprehension in students at the primary level, through the carrying out of the work entitled Reading and analysis of informative texts (news) to improve reading skills in primary school students, which is also an activity aimed at improving the comprehension of texts, specifically the competence: Read various types of texts, as established by the National Basic Education Curriculum (CNEB), in the area of communication. The methodology used is that of a descriptive study, based on theoretical research as a basis for its subsequent execution, based on the consideration of reading as a process by which a written text is decoded and interpreted to find the information it contains, either literally, inferring the content or confronting it from previously acquired ideas and knowledge. All this with the purpose of contributing to the improvement of the reading comprehension of primary school students, in a context in which teachers have the obligation to develop actions in search of the improvement of the educational system. That is why, during the development of the learning session, various strategies were used to make the reading process efficient, interesting, fun and generate new concerns in the student, in this way, to become a person capable not only of building himself as a human being, full of all his potentialities, but also of building and rebuilding his world according to his own needs, but always considering the context, the same that it shares with its peers and that also try to give form and background to a world in constant change and movement. It was concluded that the reading of informative texts is a process aimed at improving the cognitive aspects of students and is better done with the use of active techniques, which, moreover, allow a better development of the processes of socialization and communication, at the same time as the sufficient mental capacity to execute the actions that allow to achieve the performances in the competition "Read different types of texts".